2018
DOI: 10.1111/bcp.13594
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin‐induced acute kidney injury in elderly Chinese patients: a single‐centre cross‐sectional study

Abstract: For the elderly Chinese patients treated with VAN, there was insufficient monitoring of SCr, too little use of VAN TDM, and lower rate of patients whose VAN though serum concentrations were not obtained at the correct time. We recommend that hospital managers increase investment in clinical pharmacists, to strengthen professional management. Patients with concomitant hyperuricaemia and on mechanical ventilation and vasopressor therapy should be paid more attention, and a higher serum albumin was determined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 32 publications
3
26
1
4
Order By: Relevance
“…Our results showed that the incidence of VA-AKI was 14.3%, however, this could be an underestimate as 998 patients were excluded due to insufficient SCr measurements, which is consistent with our previous research ( Pan et al, 2018 ). Therefore, our results may have missed a number of VA-AKI patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that the incidence of VA-AKI was 14.3%, however, this could be an underestimate as 998 patients were excluded due to insufficient SCr measurements, which is consistent with our previous research ( Pan et al, 2018 ). Therefore, our results may have missed a number of VA-AKI patients.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, vancomycin and piperacillintazobactam are among the most commonly prescribed antibiotics in American hospitals, which are associated with significant increases in the incidence of AKI compared to vancomycin monotherapy or other empirical combinations (Balci et al, 2018;Carreno et al, 2018;Ide et al, 2019;Avedissian et al, 2020;Ciarambino et al, 2020). In contrast, previous studies have shown that, in China, the most common antibiotic combinations with vancomycin are carbapenems (Pan et al, 2017;Pan et al, 2018). Liang et al found that vancomycin nephrotoxicity was significantly correlated with the trough concentration and reported the first cut-point as 13 mg/L for the Chinese population (Liang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of VANT in the general adult patients was 4.7-15.4%, [8][9][10][11] whereas the rate was 15.8-29% in elderly patients. 6,12 With the aging of our society, VANT in elderly patients is worthy of more attention. 12 Previous studies indicate that age, 7 mechanical ventilation, 12 intensive care unit (ICU) admittance, 13 vancomycin trough concentration, 9,14-17 dose, 15 length of therapy, 9,17 infusion method (continuous or intermittent infusions), 18,19 cirrhosis, 14 hypertension, 20 hyperuricemia, 12 shock, 6 heart failure, 6 concomitant medications, vasopressor drugs, 16,17 aminoglycosides, 9,21 contrast agents, 22,23 piperacillin/tazobactam (PTZ), 24,25 furosemide, 3,11 amphotericin B, 26 and the Acute Physiology and Chronic Health Evaluation II (APACHE-II) 21,27 are risk factors associated with VANT.…”
mentioning
confidence: 99%
“…Interestingly, as seen in this study, certain biochemical markers were inferred to be important in the established vancomycin dose prediction model, including UA, PLT, TP, CRP, WBC, RBC, HCT, and Hb. Among them, UA was considered as a marker of kidney disease [33], and hyperuricemia was revealed as an independent risk factor for vancomycininduced acute kidney injury [34]. Thrombocytopenia can be caused by vancomycin-dependent antibodies produced by immune mechanisms [35].…”
Section: Discussionmentioning
confidence: 99%